Evaluating digital transformation in small and medium enterprises using the Alkire-Foster method - Luís L. Moreira; Sofia S. Pinto; Leonardo Costa; Nuno Araújo (Heliyon)
The digital technology transition fosters the flexibility of companies and their ability to respond quickly to market changes. However, Small and Medium-sized Enterprises (SMEs) seem to be particularly challenged by digital transformation. The Alkire-Foster (AF) method was employed to analyze the integration profiles of digital technology in SMEs. Individual and group average partial and composite indicators were computed, as well as group measures of digital technology integration, to benchmark individual companies and groups. Additionally, a linear regression was used to examine how individual overall composite scores of digital technology integration are influenced by dimensions of individual digital technology integration enablers and other contextual variables. The results indicate that most companies possess the digital infrastructure necessary for this integration. However, there is room for improvement in terms of supply and demand of digital skills. This study contributes to research by applying an existing tool, the AF method, in a novel context: measuring digital technology integration in SMEs. The AF method facilitates effective benchmarking at both individual and group levels.